Interventions for Cardiovascular Patients with Type D Personality: A Systematic Review. Issue 4 (22nd March 2016) - Cao, Xi; Wong, Eliza M. L.; Chow Choi, Kai; Cheng, Li; Ying Chair, Sek
ABSTRACT: Background: Cardiovasculardisease (CVD) is a major cause of death worldwide. Type D personality, a newly identified risk factor for cardiac outcomes, can deteriorate the health outcomes of CVD patients. Several interventional studies have been conducted on CVD patients with type D personality. Aim: To provide the best available evidence of the effects and characteristics of interventions applied to cardiac patients with type D personality. Methods: Experimental studies on the effects of interventions for cardiac patients with type D personality were reviewed. English and Chinese electronic databases were searched from inception to December 2014. The eligibility and quality of each article were reviewed by two independent reviewers. The outcomes of interest included psychological health (anxiety & depression), physical functioning, and quality of life. Data were synthesized in a narrative form rather than meta‐analysis because of the heterogeneity of studies and the insufficient data for statistical pooling. Results: Four studies (one randomized controlled trial and three single‐group pre‐ and posttests) involving 967 cardiac patients were identified. The quality of included studies was moderate, with three studies rated as fair and one study rated as poor. Cardiac rehabilitation programs were the interventions identified in all the included studies, with main components of physical exercise, patient education, psychological intervention, and individual counseling. The findings of this review indicated that cardiac rehabilitation can significantly reduce anxiety and depression, improve physical functioning, and quality of life in cardiac patients with type D personality. The evidence of optimal duration, frequency of interventions, and length of each session was not established. Linking Evidence to Action: This review provides preliminary evidence for the use of cardiac rehabilitation as an effective intervention to improve health outcomes in cardiac patients with type D personality. The optimal delivery format of the intervention for cardiac patients with type D personality needs to be explored.